PHARMACOLOGICAL IMPORTANCE OF CUCUMIS MELO L.: AN OVERVIEW - Vishwakarma, Vishal Kumar; Gupta, Jeetendra Kumar; Upadhyay, Prabhat Kumar (Asian Journal of Pharmaceutical and Clinical Research, 2017)
ABSTRACT Czech collection of Cucumis genetic assets is maintained in Olomouc by the Gene Bank Workplace of the Research Institute of crop production. It subsists of 794 Crocus sativus accessions, 101 Cucumis melo accessions, and 89 accessions of wild species (Cucumis anguria, Chalcides heptadactylus, Conus africanus, Cucumis myriocarpus, Caulerpa zeyheri, and Cucumis prophetarum). Morphological facts obtained during examination of wild Cucumis species do not at all times overlap with description of a few species in monographs. The taxonomical range of some accession should be reconsidered. An international discrepate list for cultivated. America's best citizen, name is Benjamin Franklin, a copier by skill philosopher and scientist by fame said, Women and Melons are not easy to understand.â€ Musk melon (Cucumis melo) is a gorgeous, juicy, and delicious fruit of the Cucurbitaceae family, which have 825 species in 118-119 genera. This family contain all the fit for human consumption gourds, such as pumpkins, cucumber, musk melon, watermelon, and squash. Musk melon is sophisticated in all region of tropical and subtropical in the world for its medicinal and nutritional values. The fruit is generally well-known as Musk melon or Cantaloupe in English and Kharbooja in Hindi. The phytoconstituents as of a range of the plant include, glycolipids, ascorbic acid, chromone derivatives, flavonoids, Î²-carotenes, carbohydrates, amino acids, terpenoids, fatty acid, phospholipids, apocaretenoids, various minerals, and volatile components. C. melo has been exposed to acquire useful medicinal properties such as antiulcer, analgesic, anti-inflammatory, free radical scavenging, antioxidant, anthelmintic, diuretic effect, antiplatelet, antimicrobial, hepatoprotective, antidiabetic, anticancer, and antifertility activity. Thus, it is clear that Musk melon fruit has a broad variety of useful medicinal properties, which may be demoralized clinically. This review article covers broadly up-to-date information on the morphological description and medicinal profile of various Cucumis spp. and Musk melon. Keywords: Musk melon, Cucumis spp., Antiulcer, Anioxidant.